Studi Pengolahan Tempe Gembus Menjadi Keripik dengan Kajian Proporsi Tepung Pelapis - Kusumaningsih, Endah; Sukardi, Sukardi; Wijana, Susinggih (Jurnal Teknologi Pertanian, 2002)
The objectives of this study is to determine the best proportion of rice flour, wheat flour, and tapioca as shell in the making of tempe gembus chips. The results showed that the proportion of rice flour 30%, wheat flour 40%, and tapioca 30% was the best treatment. The product had characteristics as moisture content 1,7243%, free fatic acid 0,391%, proteins 7,3471%,Â  broken ability 0,2624 kg/cm2, output 65,9471%, crispiness, taste, appearance, and aroma prefered by panelists. Â  Keywords: tempe gembus, chips, flour proportion